Journal of Cyprus Studies (JCS) - Kıbrıs Araştırmaları Dergisi Vol.: 12 No: 30 (2006) - N/A (Doğu Akdeniz Üniversitesi Kıbrıs Araştırmaları Merkezi (DAÜ KAM): Eastern Mediterranean University Center for Cypriot Studies, 2006)
[Abstract Not Available]
ENGLISH: The Journal of Cyprus Studies (JCS), ISSN: 1303-2925, is a publication of EMU-CCS (Centre for Cyprus Studies) which was launched in 1995. It is multi-disciplinary, refereed and bilingual journal (both in English and Turkish) published biannually. The Journal of Cyprus Studies is dedicated to the scholarly study of all aspects of Cyprus issues at a global level. It plays an active role in the development of an authoritative archive and bibliography of sources and the provision of a scholarly, academic forum for the analysis, exchange, and critique of ideas on social, cultural, historical, environmental, political and legal matters relevant to the past, present or future of Cyprus. TÜRKÇE: Kıbrıs Araştırmaları Dergisi, ISSN: 1303-2925, - Doğu Akdeniz Üniversitesi - Kıbrıs Araştirmaları Merkezi'nin yayın organı olup, disiplinler arası Kıbrıs ile ilgili Türkçe veya İngilizce özgün ve evrensel boyutta çalışmalara yer veren hakemli bir dergi olup yılda iki kez yayımlanmaktadır. Yayın hayatına 1995'de başlayan Kıbris Araştirmaları Dergisi (JCS), Kıbrıs ile ilgili bilimsel özgün makalelerin yanısıra, tanıtım yazılar, güncel bilimsel etkinlikler ile ilgili haberler, raporlar ve arşiv belgelerine yer vermektedir. JCS, İngilizce ve Türkçe olarak iki dilde yayımlanmaktadır.
Keywords: Dergi - Kıbrıs Araştırmaları (Journal - Cyprus Studies); Dergi - Kıbrıs - Kültür - Sanat - Tarih - Edebiyat (Journal - Cyprus - Culture - Arts - History - Literature); Dergi - Kıbrıslı, Kıbrıs Çalışmaları (Journal - Cypriot Studies)